Predominant Frequency in Near-Field Strong Ground Motion by Analysis of Displacement Response Spectra - Morales, Cesar A. (2024)
A literature review on the spectral content of seismic ground motion indicates that a clear predominant frequency in earthquakes is very difficult to define. Here, it is considered that this has been so because the usual seismic record or response quantity is always employed: acceleration. In this work, an attempt is made to define a single predominant frequency for strong seismic ground motion in the near field with a different idea. It is considered that this is possible if the concentration is on displacement rather than on ordinary acceleration. In particular, relative displacement response spectra will be studied, instead of the common acceleration one, and the existence of clear and neat maximum spectral displacements around, statistically, a single and general proposed predominant frequency will be investigated for a set of twenty very strong (magnitude larger than 6.5 MW) world events.